Linguagem e gênero em propostas Ã Constituinte - Magalhães, Izabel (Cadernos de Linguagem e Sociedade, 2010)
In this paper, I analyse a corpus of women's proposals to the 1988 Brazilian Constitution. These written texts show linguistic traces associated with heterogeneous orders of discourse. We can interpret in them meanings associated with women's struggle for social and political identity. In addition, we can find men's presuppositions carrying naturalized ideologies proper to patriarchal society. At the end of the paper, I comment on the need to develop Critical Language Awareness in Brazilian women.